BIMBINGAN BELAJAR DAN KARIR BERBASIS KEARIFAN LOKAL DAN NILAI KELUARGA - I MADE OLAS ASTAWA (Purwadita : Jurnal Agama dan Budaya, 2017)
The  strength  of  a  nation  depends  on  the  strength  of  its  education  system,  as  has  been demonstrated in several countries in Eastern Europe, Russia, China, India, and Latin America. One element of education that have strategic relevance is career guidance and counseling services in  education,  both  formal,  nonformal  or  informal.  Career  guidance  services  are developed conceptual  and  systemic  will  support  the  implementation  of  a  strong  educational  system  and capable  of  producing  human  resources  which  in  turn  will  become  a  skilled  work  force  and productive. Career development can contribute to the quality of employment and economic growth, particularly  in  terms  of:  (1)  efficient  use  of  funds  in  education  and  training  to  improve  the achievement  of  the  program, (2)  the  efficiency  of  the  labor  market  with  increased  placements and  ritensi  work  and  reduce  the  waiting  period  and  unemployment  ,  (3)  lifelong  learning, workforce  development,  sustainability,  employment  by  increasing  participation  in  education and training, (4) the achievement of social goals, with increased activities in all elements of the population in  education,  training,  and employment,  (5)  social  justice,  to  help individuals  and groups  in  overcoming  obstacles  in  gender,  ethnicity,  age,  disability,  social  class,  institutional learning and work.